Assessing the prospect of using Tahkim as a Shariah‐compliant ADR for resolving construction disputes - Arifin, Muhammad Ariffuddin; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Hasan, Sharina Farihah; Mohd Fauzi, Puteri Nur Farah Naadia; Aripin, Srazali (University of Lagos, Nigeria, 2016)
Conventionally, arbitration is deemed as the most frequently used alternative dispute resolution (ADR) mechanism for settling construction related disputes. In Islam a similar approach in ADR, is known as Tahkim. While the practice and procedures in arbitration are well established, but not much is known about Tahkim. In line with the interest of the business community to seek ways to adopt Shariah-compliant practice and procedures it is considered important for the prospect on using Tahkim in settling construction related disputes to be assessed. This paper reports on a study to assess the prospect of using Tahkim as a Shariah compliant ADR for resolving construction disputes. Methodology adopted for the study combines review of literature and interviews with Shariah, legal and construction experts. The outcome of the study suggests that Tahkim has the potential to be used for settling construction related disputes.